Murder comes to call - Ellicott, Jessica (Ellicott, Jessica. Beryl and Edwina mystery., 2020)
When a judge who recently ruled on her reckless motoring case is found dead in what appears to be a burglary gone wrong, adventuress Beryl and her no-nonsense partner, Edwina, search for clues to prove a gardener's innocence.